SIFAT KHABARIYAH ALLAH PERSPEKTIF ABU Al-HASAN AL-ASY’ARI: ANALISIS KITAB AL-IBANAH ‘AN USHUL AD-DIYANAH (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2022)
One form of faith is to believe that Allah has the attributes He wants. Of course there must be clear communication to the servant and his Lord so that the two activities are integrated in achieving true faith. Therefore, the researcher also aims to find out and examine how the Central Aqidah thought of Imam Abul Hasan Al-Asy'ari in the case of the Khabariyah Nature of Allah in analyzing the book of Al-Ibanah An Ushul Ad Diyanah. The questions to be answered through this research are How are the various characteristics of Allah's Khabariyah in Al-Ibanah An Ushul Ad Diyanah?, What are the thoughts of Imam Abul Hasan Al-Asy'ari about the nature of Allah's Khabariyah in the book of Al-Ash'ari. Ibanah 'An Ushulid Diyanah?, How to Approach the Interpretation of the Khabariyah Nature of Allah in the Book of Al-Ibanah' An Ushulid Diyanah? to answer these questions, the researchers used a library approach. The research method used is library research. The primary data source is the book of Al-Ibanah An Ushul Ad Diyanah and the secondary data is the translation of Al-Ibanah An Ushul Ad Diyanah and other books that are relevant and relevant to the topic of discussion. The data analysis technique in this study used descriptive analysis methods and content analysis methods. The results of this study that can be concluded are that the nature of Allah's Khabariyah is what is meant according to His word, the meaning He wants, the meaning that is purified from touching, dwelling, residing, directional and moving as well as meaning that is far from all the nature of creatures like Allah. have hands, feet, eyes and face. In determining these properties, Al-Asy'ari uses two method approaches, namely the tafwidh and takwil methods. Keywords: Khabariyah Nature of Allah, Kitab Al-Ibanah 'An Ushulid Diyanah